2019
DOI: 10.1016/j.jpeds.2019.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Early increase in body mass index and cardiometabolic risk in adolescence

Abstract: Early increase in body mass index and cardiometabolic risk in adolescence To the Editor: In an assessment of the influence of the weight gain trajectory from birth to 14 years old, Barraclough et al found that an early increase in body mass index (BMI) above the 90th percentile before 3 years of age resulted in an unfavorable cardiometabolic risk profile in adolescence, compared with children with a late increase in BMI. 1 This finding is important because early identification of children with likely future ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…AR may represent a critical window of development or may simply be an epiphenomenon of early rebound of BMI occurring in children who were already in higher BMI percentiles ( 32 , 33 , 34 ). Previous studies have looked at the BMI pattern of the percentile curves constructed cross-sectionally, whereas studies using longitudinal data have shown that many children with early AR had a normal or even low BMI at or before the AR, independent of BMI at AR age, followed by an increased BMI after AR ( 29 , 34 , 35 , 36 ).…”
Section: Adiposity Reboundmentioning
confidence: 99%
“…AR may represent a critical window of development or may simply be an epiphenomenon of early rebound of BMI occurring in children who were already in higher BMI percentiles ( 32 , 33 , 34 ). Previous studies have looked at the BMI pattern of the percentile curves constructed cross-sectionally, whereas studies using longitudinal data have shown that many children with early AR had a normal or even low BMI at or before the AR, independent of BMI at AR age, followed by an increased BMI after AR ( 29 , 34 , 35 , 36 ).…”
Section: Adiposity Reboundmentioning
confidence: 99%